Strong correlations between the exponent α and the particle number for a Renyi monoatomic gas in Gibbs' statistical mechanics - Plastino, Ángel Luis (2017)
Appealing to the 1902 Gibbs formalism for classical statistical mechanics (SM)-the first SM axiomatic theory ever that successfully explained equilibrium thermodynamics-we show that already at the classical level there is a strong correlation between Renyi's exponent α and the number of particles for very simple systems. No reference to heat baths is needed for such a purpose.